Catalytic Role of Money in Macroeconomic Engineering - Chiselebwe Ng’andwe (Current Topics on Business, Economics and Finance Vol. 1, 2023)
The purpose of this chapter is to demonstrate the strategic catalytic role of money in macroeconomic engineering which entails accurate identification and prudent organization of all factors of production to optimize macroeconomic outcomes. It was observed that the existing growth theories suffer from serious under specification of critical factors that have a bearing on economic growth. The stylized factors of production are duly recognized as the primary factors in the core or primary production arena which is a subset of the macroeconomic engineering platform that includes all factors with a bearing on macroeconomic outcomes. In terms of their functional attributes, the macroeconomic engineering factors fall into four categories: a) Primary factors: Labour, land, and capital which are employed in the core production arena; b)The organizational agents covering Government and entrepreneurs who employ primary factors in the production arena; c) Auxiliary factors with a bearing on performance of primary factors and (or) organizational agents are technology and Government Policy which, under macroeconomic engineering, is distinguished from Government as employer of primary factors and producer of public goods; and d) Catalytic factor, money which does not directly enter the production arena, but promotes and enhances the interactions of other factors. Building on Ng’andwe (1981,2020) who showed that in developing economies with mass unemployment, expansionary monetary policy can lead to increases in real output with minimal inflation, the theoretical mathematical model demonstrates the broad transmission channels through which money impacts on output in a way that makes it the most potent policy variable to spark/ stimulate and sustain economic growth. Expansionary monetary policy should, therefore be employed by developing countries as the lead economic policy for growth. However, the macroeconomic engineering solutions prescribed here are premised on availability of a credible financial intermediation system. In many developing countries with dysfunctional financial systems, the strategy of expansionary monetary policy should be preceded by comprehensive financial sector reforms on the scale experienced by the Asian Tigers during their successful economic reforms.